Pengaruh Perasan Buah Salak (Salacca Edulis) terhadap Frekuensi Defekasi dan Lamanya Diare pada Rattus Norvegicus - ALVIANA, FIFI (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2019)
Salak (Salacca edulis) is one traditional medicine to treat diarrhea. The content of fruits in the form of tannins and flavonoids that may play a role in overcoming diarrhea. This study aims to determine the effect of salak fruit juice (Salacca edulis) on defecation frequency and duration of diarrhea in rats (Rattus norvegicus strain (Wistar)). This study used a sample of white rats wistar strain as much as 30 individuals. The frequency was measured from 1 hour of oleum ricini. Results of measurements performed data analysis using Kruscal-Wallis test and Mann-Witney. The results of this study showed fruit juice salak (Salacca edulis) showed the first frequency decline in at 7 times / hours becomes 1 times/ hours (p = 0.001) and duration of diarrhea first occurs in 1 hour is 1.25 Â± 0.462 hours (p = 0.001). It can be concluded that there are significant salak fruit juice (Salacca edulis) on defecation frequency and duration of diarrhea in rats (Rattus norvegicus strain (wistar)).